2021
DOI: 10.1590/1983-21252021v34n402rc
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Parameters Estimated for Fresh Corn Under Different Nutrient Availability1

Abstract: The objective of this work was to estimate and compare phenotypic and genetic parameters after three cycles of intrapopulation recurrent selection for fresh corn grown under three nutrient availability conditions. Three experiments derived from the same population (MV-003) were conducted to assess the ability of progenies to absorb nutrients, one under adequate fertilization (control; MV-006), one under low nitrogen availability (N; MV-006N), and one under low phosphorus availability (P; MV-006P). The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Some experimental hybrids have more interesting characteristics to be marketed in trays, mainly shorter lengths; however, the larger ear diameters of the hybrids DH81 and DH82 resulted in higher grain weights (97.5-85.5 g, respectively), being more attractive to consumers. Ribeiro et al (2016) found that there is a low effect for these variables with the reduction of P doses between 75 and 150 kg ha -1 of P 2 O 5 , with increments of only 1.51 cm and 0.38 mm, respectively, what may also indicate a low number of alleles involved and a very small genotype by environment interaction, in this case, confirmed by the non-interaction of the diameter variable and low influence on the length under selection for low P availability, as stated by Resende et al (2021).…”
Section: Degreesmentioning
confidence: 57%
See 1 more Smart Citation
“…Some experimental hybrids have more interesting characteristics to be marketed in trays, mainly shorter lengths; however, the larger ear diameters of the hybrids DH81 and DH82 resulted in higher grain weights (97.5-85.5 g, respectively), being more attractive to consumers. Ribeiro et al (2016) found that there is a low effect for these variables with the reduction of P doses between 75 and 150 kg ha -1 of P 2 O 5 , with increments of only 1.51 cm and 0.38 mm, respectively, what may also indicate a low number of alleles involved and a very small genotype by environment interaction, in this case, confirmed by the non-interaction of the diameter variable and low influence on the length under selection for low P availability, as stated by Resende et al (2021).…”
Section: Degreesmentioning
confidence: 57%
“…Therefore, the hybrids DH62, DH71, DH82 and DH102 presented a higher efficiency and responsiveness to P for unhusked and husked ear weight, based on the performance of the control (AG1051), and a higher chance of success in corn markets focused on growers with low to high technological levels (Table 4). Resende et al (2021) reported difficulties for generation of variability in hybrids under low nitrogen and P availability conditions, as breeding programs always prioritized cultivars for high P availability; thus, allelic combinations for low P availability conditions would be more difficult to be identified currently.…”
Section: Degreesmentioning
confidence: 99%
“…The experiment was conducted at the Universidade Estadual de Goiás (UEG), in Ipameri, GO, Brazil, during the summer, after five selection cycles. The corn population used for the formation of progenies was from the MV-003 population, obtained through complex crossing between the imported hybrids CN19-50 and CN 23-50, which are sweet corn hybrids (susu), and the double experimental hybrid HD17 (SuSu) of the UEG plant breeding program (MELHORVE), which present more adequate characteristics to the national market and higher starch contents (SuSu), as shown by Resende et al (2021). The progenies were preselected and then subjected to five selection cycles, using intrapopulation recurrent selection of half-sib progenies.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there is only one corn cultivar focused on fresh consumption in the market, the BRS3046 (conventional), among the 98 corn cultivars available in the 2020-2021 crop season; four cultivars available for this niche were excluded and the number of cultivars in relation to previous crop season decreased approximately 45% (PEREIRA FILHO; BORGHI, 2021), which restricts this crop. Therefore, the development of improved populations, hybrids, and varieties with open pollination are essential to meet the demands of growers and consumers and, generate information and quality genotypes for fresh consumption (RESENDE et al, 2021). Therefore, the recurrent selection method is a viable option by selecting the best progenies over several cycles to obtain successive gains in each cycle without depleting the genetic variability of the population (HALLAUER; CARENA; MIRANDA FILHO, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation